Emancipation Against All Odds? The Conservatism Charge to Deliberative Democracy Reconsidered - Andreas Schäfer; Wolfgang Merkel (Journal of Deliberative Democracy)
Although deliberative democracy has been conceptualized as an emancipatory project, it has since been accused of producing conservative outcomes. This article provides a critical and comprehensive review of the conservatism charge by asking: Does deliberative democracy’s mechanisms systematically undermine its emancipatory claim? What are the persistent and emerging obstacles to the realization of deliberative democracy's emancipatory potential? To answer these questions, we develop an analytical framework that identifies deliberative democracy’s problematic mechanisms. We argue that the conservatism charge may be sorted into three dimensions: social, substantial, and temporal. The three dimensions conceptually comprise the questions of who deliberates, how deliberation unfolds, and what effects deliberative procedures have on the process of emancipation in time. The article demonstrates that although deliberative processes have the potential to reach emancipatory aims even under unfavorable circumstances, adverse social conditions can produce conservative effects through deliberative practices. In order to avoid or mitigate those tendencies and promote the genuinely critical potential of deliberative practice, measures and research desiderata are discussed on both setting and system levels.